Low firing temperatures and high ferroelectric properties of (Ba0.85Ca0.15)(Ti 0.90Zr0.10)O3 lead-free ceramics synthesized by the combustion technique - Kornphom, Chittakorn; Vittayakorn, Naratip; Bongkarn, Theerachai (My University, 2016)
This work studied the effect of firing conditions on phase formation, microstructure and electrical properties of (Ba0.85Ca0.15)(Ti0.90Zr0.10)O3;(abbreviated as BCTZ) ceramics, which were synthesized through the combustion technique. To reduce the reaction temperature, glycine was used as fuel with a ratio of raw material: glycine (1:1.11). BCTZ samples were calcined at 900-1200°C for 2 h and sintered at 1350 -1550°C for 2 h. Ultrafine BCTZ powder and single peroveskite phase were achieved from the sample calcined at 1050°C for 2 h.These results were obtained at a lower temperature and with shorter dwell time than those obtained using the solid state reaction method by ∼150°C and 1 h, respectively. The BCTZ ceramics exhibited a coexistence of rhombohedral and orthorhombic phase in all samples. The average particle size and the average grain size increased from 172 to 295 nm and 0.82 to 2.57 μm, respectively, when firing temperatures increased. The highest density (5.76 g/cm3), highest dielectric constant (εr ≅ 4485 and εmax ≅ 14897) and best ferroelectric properties (Pr ≅ 18.47 C/cm2 and EC ≅ 4.52 kV/cm) were obtained from the sample sintered at 1450°C for 2 h.
Keywords: BCTZ; combustion technique; crystal structure; dielectric properties; ferroelectric properties; microstructure